Reusable Packing. Generic Products and the Recycling Proces - Altman, Rick (Iluminace, 2002)
The study is devoted to genres and subgenres in the history of culture with a focus on film. The evolution and shift in the designation of each genre and the emergence of new terms. Differences between genres and their overlap.
Keywords: film genres; film aesthetics; cultural history; film history